Updating the emotional content of working memory in social anxiety. (September 2015) - Segal, Adva; Kessler, Yoav; Anholt, Gideon E.
Abstract: Background and objectives: Cognitive accounts suggest that information processing biases have an important role in the etiology and maintenance of social anxiety (SA). Empirical evidence support this notion has been established in variety of cognitive domains. Yet, it is still not known how social anxious individuals process emotional content in working memory (WM). Maladaptive WM updating may influence emotion regulation and anxiety during social situations in SA. Thus, the aim of the present study was to explore biases when updating emotional content in SA. Methods: 31 participants with high SA and 34 control participants performed an emotional 2-back task. Biases were assessed by intrusion cost in reaction times, which reflects the conflict between the inhibition of irrelevant content and the activation of relevant content. Results: Results revealed a diminished intrusion cost in reaction times for irrelevant positive content in the high, but not in the low SA group. No differences were found for negative or neutral content. Limitations: In the present study we used an analogue sample of students with high SA rather than a true clinical sample. Further research is needed to examine WM updating in clinical population. Conclusions: These findings suggest that individuals with SA are better at inhibiting irrelevant positive information, a maladaptive cognitive bias that may prevent positive feedback from entering the cognitive system. This cognitive bias in WM may play a role in the etiology and maintenance of SA. Highlights: We explored working memory (WM) updating biases in social anxiety (SA), using an emotional 2-back task. Findings revealed a diminished intrusion cost for positive content, but not for negative or neutral content, in the high SA group compared with the low group. Socially anxious individuals are better at inhibiting irrelevant positive content in WM. This bias may prevent positive feedback from entering the cognitive system, resulting in up-regulation of negative feelings and anxiety.